Stent versus Balloon Dilation for the Treatment of Dominant Strictures in Primary Sclerosing Cholangitis: A Systematic Review and Meta-Analysis - Marina Tucci Gammaro Baldavira Ferreira; Igor Braga Ribeiro; Diogo Turiani Hourneaux de Moura; Thomas R. McCarty; Alberto Machado da Ponte Neto; Galileu Ferreira Ayala Farias; Antônio Afonso de Miranda Neto; Pedro Victor Aniz Gomes de Oliveira; Wanderley Marques Bernardo; Eduardo Guimarães Hourneaux de Moura (Korean Society of Gastrointestinal Endoscopy, 2021)
Background/Aims The endoscopic management of primary sclerosing cholangitis (PSC)-associated dominant strictures remains challenging. This systematic review and meta-analysis aimed to compare balloon dilation and stent placement in the treatment of dominant strictures among PSC patients. Methods Literature searches on MEDLINE, EMBASE, Cochrane CENTRAL and Lilacs/Bireme were performed for studies published until December 2020. Measured outcomes included clinical efficacy, stricture recurrence, cumulative recurrencefree rate, transplant rate, 5-year survival rate, and adverse events (i.e., pancreatitis, cholangitis, bleeding, perforation and death). Results A total of 5 studies (n=467) were included. Based on pooled analyses, there were no differences in clinical efficacy (risk difference [RD], -0.13; 95% confidence interval [CI], -0.58 to 0.33; I2=93%) or transplant rates (RD, -0.09; 95% CI, -0.19 to 0.01; I2=0%); however, the risk of occurrence of adverse events was lower with balloon dilatation than with stent placement (RD,-0.34; 95% CI, -0.45 to -0.23; I2=61%). Among the types of adverse events reported, only the rates of cholangitis/bacteremia were significantly lower in balloon dilation patients (RD, -0.19; 95% CI, -0.25 to -0.13; I2=51%). Conclusions Compared to balloon dilation, stent placement for dominant strictures in PSC appeared to have higher complication rates without significant differences in efficacy.